2003
DOI: 10.3354/meps251191
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the biochemical composition of the chaetognath Parasagitta elegans from the hyperbenthic zone of Conception Bay, Newfoundland

Abstract: The biochemical composition of the chaetognath Parasagitta elegans from the hyperbenthic zone of Conception Bay, Newfoundland, was determined from April 1997 to June 1998. Lipid and carbohydrate levels (% dry weight) were relatively high in the spring and summer and low in the fall and winter. Conversely, the relative protein level was low in the spring and summer and high in the fall and winter. Carbon level was generally high in the spring and summer of 1997 but low from fall to the following spring, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
0
24
1
Order By: Relevance
“…However, modelling of over 10 yr of biological and physical data has revealed that the timing of the initiation of the spring phytoplankton bloom is independent of temperature (Tian et al 2003), while bacteria and especially zooplankton growth may be suppressed in the spring (Pomeroy et al 1991). Consequently hyperbenthic and benthic animals are the recipients of significant portions of the productivity (Choe et al 2003, Stead & Thompson 2003. The quality of the settling material should be high, as polar microalgae produce high levels of PUFA (Skerratt et al 1995, Henderson et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…However, modelling of over 10 yr of biological and physical data has revealed that the timing of the initiation of the spring phytoplankton bloom is independent of temperature (Tian et al 2003), while bacteria and especially zooplankton growth may be suppressed in the spring (Pomeroy et al 1991). Consequently hyperbenthic and benthic animals are the recipients of significant portions of the productivity (Choe et al 2003, Stead & Thompson 2003. The quality of the settling material should be high, as polar microalgae produce high levels of PUFA (Skerratt et al 1995, Henderson et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…crustaceans and pteropods, show a pronounced lipid accumulation during summer phytoplankton blooms (Hagen 1988, Hagen & Schnack-Schiel 1996, Gannefors et al 2005, Böer et al 2005. There is some evidence of lipid accumulation in the boreal chaetognaths Parasagitta elegans and Eukrohnia hamata during the spring/summer phytoplankton blooms (Båmstedt 1978, Choe et al 2003) and in Arctic ctenophores during feeding on copepods (Falk-Petersen et al 2002, Lundberg 2003. While the Arctic is characterized by large populations of diapausing copepods, which overwinter in deep waters, Antarctic waters are usually inhabited by large euphausiid populations, which do not undergo diapause but remain in surface waters during winter .…”
Section: Polar Biomementioning
confidence: 99%
“…The male gonads (testes and seminal vesicles) produce and secrete the sperm, whilst the female gonads (ovaries and seminal receptacles) produce the ova and receive sperm from a sexual partner (Alvarino 1992). The seminal receptacles are known to develop in the later stages of the maturation cycle, shortly before reproduction (Russell 1932, Choe et al 2003. To assess their state of maturity, Parasagitta elegans individuals from each month were stained with Borax Carmine solution, and the development of their ovaries and seminal receptacles, and the amount of sperm in their tails, were observed under a stereomicro scope.…”
Section: Maturity Conditionmentioning
confidence: 99%
“…may display similarly marked adaptations to seasonality (e.g. Choe et al 2003, Dale et al 2006. In this study we have examined the seasonal ecology and life history of the chaeto gnath Parasagitta elegans var.…”
Section: Introductionmentioning
confidence: 99%